Issues and Challenges of Teaching and Learning in 3D Virtual Worlds: Real Life Case Studies - Pfeil, Ulrike; Ang, Chee Siang; Zaphiris, Panayiotis (My University, 2009)
We aimed to study the characteristics and usage patterns of 3D virtual worlds in the context of teaching and learning. To achieve this, we organised a full-day workshop to explore, discuss and investigate the educational use of 3D virtual worlds. Thirty participants took part in the workshop. All conversations were recorded and transcribed for analysis. Thematic analysis was carried out to identify prominent issues and topics. We found that to fully utilise 3D virtual worlds for teaching and learning, students, tutors and educational institutions face a number of socio-psychological, pedagogical and technological challenges. The paper highlights and discusses the issues that emerged from the workshop, supporting them with real life experiences and case studies provided by the workshop participants.
Keywords: 3D virtual worlds; Teaching and learning; Pedagogy; Case study